Effect of Social Media Influencer Marketing on Consumers' Purchase Intention and the Mediating Role of Credibility. Issue 4 (19th November 2020) - , Saima; Khan, M. Altaf
Abstract: A new digital marketing tool that has emerged today is that of social media influencer marketing. Social media influencers are those individuals who shape consumers' perceptions regarding a brand or product through photos, videos and other updates on social media platforms. This research paper is an attempt to identify the effect of various attributes of social media influencers on their credibility and eventually on purchase intention of consumers in Delhi NCR, India. An online questionnaire was used to collect data through Google Forms and the size of the sample was 76. Quota sampling technique was used, and structural equation modeling through SmartPLS 3 was used for data analysis. The findings reveal that trustworthiness, information quality and entertainment value have significant direct effects on the credibility of influencers as well as significant indirect effects on the purchase intention of consumers. Also, the purchase intention of consumers is directly affected by an influencer's trustworthiness and credibility.